Disruption of the Covid-19 pandemic in micro business marketing communication: A case study on Fransis Pizza & Dimsum Shumpit - Revta Fariszy; Virginia Ayu Sagita (The Indonesian Journal of Communication Studies, 2022)
The COVID-19 pandemic has a massive impact on economic sectors, incredibly individual jobs. In order to survive, those people have to think of another way to get income; business is one of them. Microbusiness is a quick solution, but the lack of marketing skills and business experience is the first challenge they have to go through. New entrepreneurs usually run a micro-business with limitations and planning without being based on marketing rules. This study aims to determine the marketing communication strategy of micro-businesses during the Covid-19 pandemic in starting a business for survival with the approach to Entrepreneurial Marketing (EM). The method used in this research is a case study with a marketing communication approach. Informant retrieval in this study is using purposive sampling. This research shows that different micro-business marketing approaches started during the pandemic, which intersects with entrepreneurial concepts and leisure-time businesses.